(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Emotions The linguist appears at the crossroads of psychology and linguistics, and became many prominent linguistics (N.A. Krasavsky1, E.Myagkova2, V.I Shakhovsky3). At the end of the twentieth century V.I. Shahovsky introduced the term "emotional" to linguistics. This direction studies the place of emotions in human activity. According to Shahovsky, "With the idea of human emotional condition, we can tell you clearly that we know who he is. During the communications process, emotional reactions show human values and goals. Understanding emotions is the key to understanding the personality of the human personality. The introduction of this term not only allowed our feelings and emotional state, but also to determine the level of description of the interviewee reflectation